Differential Effects of Viremia and Microbial Translocation on Immune Activation in HIV-Infected Patients Throughout Ritonavir-Boosted Darunavir Monotherapy. Issue 17 (May 2015) - BenMarzouk-Hidalgo, Omar J.; Torres-Cornejo, Almudena; Gutiérrez-Valencia, Alicia; Ruiz-Valderas, Rosa; Viciana, Pompeyo; López-Cortés, Luis F.
Abstract : Abstract: The purpose of this article is to evaluate the evolution of microbial translocation (MT) and its role in CD4 + and CD8 + T cells immune activation (IA) in HIV-1-infected patients on ritonavir-boosted darunavir monotherapy (mtDRV/rtv). Prospective study of consecutive HIV-1-infected patients switched to mtDRV/rtv as a simplification regimen. Subjects were classified according to the virological behavior during a 24-month follow-up as continuous undetectable viral load, blips, intermittent viremia, and virological failure (VF). MT was evaluated by plasma LPS and 16S genomic rDNA (16S rDNA) levels, whereas IA was assessed by the coexpression of HLA-DR and CD38 in CD4 + and CD8 + T cells, and plasma sCD14 levels. Seventy-one patients were included in this substudy of the MonDar cohort (ClinicalTrials.gov: NCT01505722). At baseline, CD4 + (ρ = −0.352, P = 0.01) and CD8 + T-cell activation (ρ = −0.468, P < 0.001) were correlated with time with viral suppression, but not with MT markers. A significant decrease in plasma LPS levels was found only in patients without VF (baseline, 77.8 vs month 24, 60.4 pg/mL; P < 0.001]. Both plasma 16S rDNA and sCD14 levels were unchanged irrespective of the viral behavior. The only variable independently associated with a decrease in CD4 + and CD8 + T cells activation was an undetectable HIV-1 viremia (β = 4.78, P < 0.001 and β = 2.93, P = 0.005, respectively). MT does not have a pivotal role in T-cell activation, at least in patients with long-term viral suppression. The viremic episodes and VF are the main factors related to CD4 + and CD8 + T-cells IA, even during mtDRV/rtv.